2021
DOI: 10.3389/fcell.2021.631623
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Wnt Signaling Pathways at the Plasma Membrane and Their Misregulation in Cancer

Abstract: Wnt signaling is one of the key signaling pathways that govern numerous physiological activities such as growth, differentiation and migration during development and homeostasis. As pathway misregulation has been extensively linked to pathological processes including malignant tumors, a thorough understanding of pathway regulation is essential for development of effective therapeutic approaches. A prominent feature of cancer cells is that they significantly differ from healthy cells with respect to their plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 259 publications
1
43
0
Order By: Relevance
“…It regulates a broad spectrum of biological processes including cell differentiation and proliferation, embryo development, or apoptosis. Furthermore, abnormal activation of the Wnt/β-Catenin pathway has been shown in different cancers including colorectal, lung, liver, or breast cancer [ 209 ]. Additionally, experiments have also demonstrated that suppression of the Wnt pathway inhibits the proliferation of cancer cells.…”
Section: Modulation Of Selected Signaling Pathwaysmentioning
confidence: 99%
“…It regulates a broad spectrum of biological processes including cell differentiation and proliferation, embryo development, or apoptosis. Furthermore, abnormal activation of the Wnt/β-Catenin pathway has been shown in different cancers including colorectal, lung, liver, or breast cancer [ 209 ]. Additionally, experiments have also demonstrated that suppression of the Wnt pathway inhibits the proliferation of cancer cells.…”
Section: Modulation Of Selected Signaling Pathwaysmentioning
confidence: 99%
“…There are 10 members of the Frizzled (FZD) protein family, which serve as receptors for both the canonical and non-canonical signaling pathways. The pairing between specific FZDs and another receptor, such as low-density lipoprotein receptor-related protein 5 or 6 (LRP5/6), receptor Tyr kinase-like orphan receptor 1 or 2 (ROR1/2) and receptor Tyr kinase (RYK), directs the downstream signaling pathway ( Azbazdar et al, 2021 ). Canonical WNT signaling is initiated by binding of WNT ligands (e.g., WNT3A and WNT10B) to a heterodimeric receptor complex formed by a Frizzled (FZD) and LRP5/6.…”
Section: Introductionmentioning
confidence: 99%
“…As reported, the Wnt signaling pathway is one of the important pathways that regulate the proliferation, differentiation, and migration of cells, 20 and dysregulation of the Wnt signaling pathway is closely associated with the development of a variety of tumors such as lung cancer, liver cancer, and breast cancer. 21 Moreover, three immune‐related pathways, including T‐cell receptor signaling pathway were also enriched, suggesting that the immune status of T cells might be associated with radiation resistance.…”
Section: Discussionmentioning
confidence: 99%